Class Association Program to Prevent Delinquency of Elementary School Children - Hamidulloh Ibda (Abjadia, 2018)
This study aims at describing the class association program in Sampangan 01 Elementary School, Semarang in preventing child delinquency. Delinquency in this study includes physical violence such as hitting friends, harsh words, smoking, hair dyeing, stealing, use narcotics and others. The results of the research, the class association as part of the partnership program for the three centers of education and family involvement in the education unit is very strategic to building families in the success of children’s education. In addition, to play a role in preventing juvenile delinquency, the class association mobilizes class independence in designing classrooms and completing class facilities. The significant impact of this class association prevents child delinquency for one semester initially there were 15 children into 3 children, supports the success of learning in schools, synergies between parents and schools, intense face-to-face communication and via telephone, parent and homeroom meetings, and parent classes. The class association also supports schools in carrying out active learning with classroom transparency media to make children comfortable learning from the work of class community members.يهدف هذا البحث لوصف برامج الرابطة الصف في مدرسة الإبتدائية الحكومية سامفانجان ۱ سيمارانج في منع جنوح الأطفال. الجنوح في هذا البحث يشتمل على عنف الجسدي كضرب الأصدقاء, والكلمات القاسية, والتدحين, وتلوين الشعر, والسرقة, واستخدام الوخدرات, وغيرها. نتائج هذا البحوث وهو: رابطة الصف جزء من التعاون البرامج بين ثلاثة مراكز التعلمية و إشراك الأسرية في وحدة التعليم الإستراتيجي جدا لأتفاق الأسر في نجاح تعليم الأطفال. بالإضافة إلى التصريف لمنع جنوح الأطفال, تقوم رابطة الصف بتحويل الإستقلالية الطبقة في تصميم الفصول الدراسية وإكمال المرافق الطبقية. التأثير الكبير لهذه الرابطة الصف هو منع الجنوح الأحداث لمدة فصل الدراسي واحد في البداية كان هناك خمسة عشر طفلا إلى ثلاثة أطفال, دعم نجاح التعليم في المدرسة, التآثر الوالد مع المدرسة, التواصل المكثف وجها من الهاتف, إجتماع الوالدين و ولي القسم, وكذالك فئة الوالدين. دعم الرابطة الصف المدارس في تنفيذ التعليم النشط بواسطة التلوين الفصول لجعلوا الأطفال بالراحة في التعليم من التحصيل الرابطة الصف.ية.